1972
DOI: 10.1107/s0567739472001147
|View full text |Cite
|
Sign up to set email alerts
|

The molecular packing of solid II cyclobutane by means of spectroscopic data and potential-energy calculations

Abstract: The molecular packing of solid II cyclobutane has been calculated starting from the knowledge of the site symmetry (point group D2) and of two possible symmetries of the primitive unit cell (D2 and D2h factor group symmetry), derived from analysis of the infrared and Raman spectra. Crystal potential energy has been calculated for 13 orthorhombic space groups using the packing program written by Williams. The calculation was based on a pairwise potential of Buckingam type, widely tested on a large number of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…These assignments are summarized in Table 6. The far infrared spectra were not as defmitive as the Raman spectra; however, the data were reasonably consistent with that previously reported by Castellucci et al [22]. For example, in the far infrared spectrum of the "light" compound, pronounced bands were observed at 100.3 and 86.7 cm-I with a possible additional one at 81.2 cm-I .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These assignments are summarized in Table 6. The far infrared spectra were not as defmitive as the Raman spectra; however, the data were reasonably consistent with that previously reported by Castellucci et al [22]. For example, in the far infrared spectrum of the "light" compound, pronounced bands were observed at 100.3 and 86.7 cm-I with a possible additional one at 81.2 cm-I .…”
Section: Resultssupporting
confidence: 92%
“…However, the spectral data reported by Castellucci et al [22] are in better agreement with our data than the data reported by Miller et al [23] Similarly, our data on cyclobutane-d8 (Fig. lOA) agrees well with that reported by Castellucci et al [22] for this isotope except that we did not observe the very weak line at 144 cm-I nor the weak broad line at 55 em-I. However, in our initial investigation we observed a weak line at 65 cm-l which disappeared with further purification of the sample.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations